2022
DOI: 10.52547/jad.2022.4.2.3
|View full text |Cite
|
Sign up to set email alerts
|

An updated checklist of spiders (Arachnida: Araneae) of Rajasthan, India

Abstract: In this review, an updated checklist of spider diversity in Rajasthan, India is presented. A total of 173 spider species from 90 genera belonging to 25 families are listed with records/descriptions originating from only 20 out of 33 districts of Rajasthan. A total of 74 taxa recorded from various districts of Rajasthan were identified only up to generic level. The maximum number of spider species were recorded from Jodhpur district (72 species), followed by Ajmer (69 species), Bharatpur (66 species), Pali (63 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…The conservation status of 99.5% of the spider species has not yet been evaluated by the IUCN globally (Seppälä et al, 2018). Despite recent research works on the diversity and distribution of spiders in India, their number is insufficient as compared to the other parts of the world (Singh, 2022b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The conservation status of 99.5% of the spider species has not yet been evaluated by the IUCN globally (Seppälä et al, 2018). Despite recent research works on the diversity and distribution of spiders in India, their number is insufficient as compared to the other parts of the world (Singh, 2022b).…”
mentioning
confidence: 99%
“…The survey of the literature revealed that the existing information on the spider diversity in two union territories, Jammu and Kashmir and Ladakh are scattered and more than half of the areas have not yet been surveyed for faunal distribution of spiders. Recently, the checklist of spider fauna have been reported from Indian States such as --Andhra Pradesh (Singh and Sharma, 2022a), Bihar and Jharkhand (Singh and Singh, 2021b), Chhattisgarh (Singh and Singh, 2021c), Goa , Haryana, Himachal Pradesh, Punjab, Chandigarh and Delhi (Singh and Singh, 2021d), Karnataka (Singh, 2022b), Madhya Pradesh (Singh and Sharma, 2022b), Maharashtra (Singh, 2022a), Odisha (Singh, 2022c), northeast India (Arunachal Pradesh, Assam, Manipur, Meghalaya, Mizoram, Nagaland, Sikkim, Tripura) (Singh and Singh, 2021e), Rajasthan , Telangana (Singh and Sharma, 2022c), Uttar Pradesh and Uttarakhand and Andaman, Nicobar and Lakshdweep (Singh and Singh, 2022d).…”
mentioning
confidence: 99%